A Variant of the Histone-Binding Protein sNASP Contributes to Mouse Lupus - Ju, Jiyu; Xu, Jia; Zhu, Yaoqiang; Fu, Xiaoyan; Morel, Laurence; Xu, Zhiwei (Frontiers in Immunology, 2019)
The Sle2c1rec1c (rec1c) sublocus is derived from the mouse lupus susceptibility 2 (Sle2) locus identified in the NZM2410 model. Our current study dissected the functional characters and the genetic basis of the rec1c locus relative to lupus when co-expressed with the Faslpr mutation, an established inducer of autoimmunity. The rec1c.lpr mice exhibited mild expansion of lymph nodes and had a normal T cell cellularity, but developed significantly glomerulonephritis and lung inflammation, indicating that the rec1c amplifies lpr-induced autoimmune pathogenesis. A variant of somatic nuclear autoantigenic sperm protein (sNASP) was identified from the rec1c interval as a substitution of two consecutive amino acid residues in the histone-binding domain, resulting in an increased binding affinity to histone H4 and H3.1/H4 tetramer. To determine the role of the sNASP rec1c allele in mouse lupus, a novel strain was generated by introducing the rec1c mutations into the B6 genome. In this transgenic model, the sNASP allele synergized with the lpr mutation leading to moderate autoimmune phenotypes and severe inflammatory pathology alterations in kidney and lung that were similar to those observed in the rec1c.lpr mice. These results establish that the sNASP allele is a pathogenic genetic element in the rec1c sublocus and mainly aggravates inflammation reaction of end organs in mouse lupus pathogenesis. It also shows the complexity of the Sle2c locus, initially mapped as the major locus associated with B1a cell expansion. In addition to Cdkn2c, which regulates this expansion, we have now identified in the same locus a protective allele of Csf3r, a variant of Skint6 associated with T cell activation, and now a variant of sNASP that amplifies autoimmune tissue pathology.